Analysis of the epidemiological trends of Tuberculosis in China from 2000 to 2021 based on the joinpoint regression model - Zhili Li; Lijie Zhang; Yuhong Liu (BMC Infectious Diseases)
Abstract Background China is ranked third globally in terms of burden and has a moderately high to high prevalence of tuberculosis (TB). This study meticulously investigated the notification rates of TB and assessed the epidemic in China from 2000 to 2021. The aim of the study was to provide robust supporting data that is crucial for enhancing TB prevention and control strategies. Methods Extensive data regarding TB notification rates in China between 2000 and 2021 was collected. The joinpoint regression model was subsequently utilized to assess the temporal trends in the notification rates of TB, which were analyzed through the annual percentage change (APC) and the average annual percentage change (AAPC). Results During the study period (2000–2021), the standardized notification rates of TB in China ranged from 38.89/100,000 to 101.15/100,000, with a significant annual average decrease of 4.43% (P < 0.05). Before the COVID-19 pandemic, a marked acceleration in this decline was observed from 2006 to 2015, with an APC of 4.62% (P < 0.05). Stratified by age and sex, the age group with the most significant annual decline in overall standardized notification rates of TB among males in China was < 15 years old, followed by 55–64 years old, and the group with the least decrease was 25–44 years old. Similarly, the age group with the most significant annual decline in standardized notification rates of TB among females was < 15 years old. Conclusions The epidemic of TB in China exhibited a downward trajectory between 2000 and 2021. However, it is imperative to prioritize the attention given to males and older adults, and to promote specific and effective prevention and control strategies for these populations.